2014
DOI: 10.1111/tpj.12550
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐genome profiling and shotgun sequencing delivers an anchored, gene‐decorated, physical map assembly of bread wheat chromosome 6A

Abstract: Bread wheat (Triticum aestivum L.) is the most important staple food crop for 35% of the world's population. International efforts are underway to facilitate an increase in wheat production, of which the International Wheat Genome Sequencing Consortium (IWGSC) plays an important role. As part of this effort, we have developed a sequence-based physical map of wheat chromosome 6A using whole-genome profiling (WGP™). The bacterial artificial chromosome (BAC) contig assembly tools fingerprinted contig (fpc) and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 53 publications
3
38
0
Order By: Relevance
“…This could hint at the presence of a genetic element controlling recombination rate that is specific for that chromosome. It was shown that recombination greatly increased from the centromere toward the telomeres on chromosome 6A ( p oursarebani et al 2014), as expected for plants with large genomes. Moreover, it was shown that a recent translocation (6VS:6AL) led to a suppression of recombination rate on 6AL ( x ie et al 2012), which could be due to the knockout of a locus involved in recombination.…”
Section: Discussionsupporting
confidence: 54%
“…This could hint at the presence of a genetic element controlling recombination rate that is specific for that chromosome. It was shown that recombination greatly increased from the centromere toward the telomeres on chromosome 6A ( p oursarebani et al 2014), as expected for plants with large genomes. Moreover, it was shown that a recent translocation (6VS:6AL) led to a suppression of recombination rate on 6AL ( x ie et al 2012), which could be due to the knockout of a locus involved in recombination.…”
Section: Discussionsupporting
confidence: 54%
“…While the number of anchored contigs to the genetic map of 5DS was considerably higher than that of 1AL physical map [15], more recent physical maps of 1BS, 1BL, and 6A reported similar percentages of contigs integrated with the genetic maps, as 77.4 %, 74 %, and 79 %, respectively [16, 18, 19]. Among these contigs, 63 were ordered within the deletion bins utilizing primarily the shared extensive homology between Ae.…”
Section: Resultsmentioning
confidence: 99%
“…Current efforts aim to generate physical maps based on BAC minimum tiling paths developed from flow-sorted chromosome arms (Paux et al, 2008) and to fully sequence these regions by 2017. So far, a single wheat chromosome has been fully sequenced (chromosome 3B; Choulet et al, 2014), while physical maps are being generated for most of the remaining 20 chromosomes (Philippe et al, 2013;Poursarebani et al, 2014). The fully sequenced and annotated 3B chromosome represents an excellent resource for wheat researchers and will serve as a benchmark for the remaining wheat chromosomes.…”
Section: Reviewmentioning
confidence: 99%